Pengaruh Harga Minyak Dunia, Indeks Dow Jones dan Indeks Hang Seng terhadap Indeks Harga Saham Gabungan Periode 2016-2020 - Beureukat, Beureukat; Andriani, Eka Yulian (Oikonomia: Jurnal Manajemen, 2021)
Purpose This study aims to analyze the effect of world oil prices, Dow Jones index, and Hang Seng index on the Composite Stock Price Index (JCI). Methodology The study was conducted using secondary data per month in the 2016-2020 period and analyzed using multiple linear regression methods. Findings The results showed that world oil price and Dow Jones index partially had a positive and significant effect on the JCI, while Hang Seng Index had no significant effect on the JCI.Suggestion Investors who want to invest should always pay attention to the movements in world oil prices and the Dow Jones index.